Fear of COVID-19 Among Patients with Inflammatory Bowel Disease as Compared to Patients with Other Gastrointestinal Conditions - Lo, Bobby; Acosta, Manuel Barreiro-de; Bernstein, Charles N.; Burisch, Johan; Ferreira, Nuno; Gearry, Richard B.; Mikocka-Walus, Antonina; Mokrowiecka, Anna; Trindade, Inês A.; Knowles, Simon R. (Turkish Journal of Gastroenterology, 2022)
Background: Although several studies have reported the impact of fears relating to coronavirus-19 on several chronic illnesses, there are few studies focused on gastrointestinal conditions. Therefore, the aim of this study was to compare the fear of coronavirus-19 in patients with inflammatory bowel disease to other gastrointestinal conditions and how the fear of COVID-19 manifests across different demographical backgrounds among inflammatory bowel disease respondents. Methods: Participants with gastrointestinal conditions (age ≥ 18) were recruited from 27 countries. Demographic, clinical, and psychosocial information was collected. An adapted scale for inflammatory bowel disease patients measuring the fear of coronavirus-19 and gastrointestinal-specific fear of coronavirus-19 was used. Results: In 831 participants (312 inflammatory bowel disease), only significant increases in gastrointestinal–fear of coronavirus-19 were found in between inflammatory bowel disease and other gastrointestinal conditions (mean [standard deviation]: 13.5 [5.5] vs 10.9 [5.0], P < .01). Among inflammatory bowel disease respondents, persons on sick leave had significantly more fear of coronavirus-19 than those employed (median [IQR], 31.0 [28.5-39.5] vs 26.0 [20.0-33.0], P = .035) and significantly more gastrointestinal–fear of coronavirus-19 compared to the employed (18.0 [14.5-22.0] vs 13.0 [9.0-17.0], P = .033) or respondents outside of the labor market (12.0 [7.0-16.0], P = .022). Persons living in a rural setting had significantly more fear of coronavirus-19 compared to persons living in regional setting (29.5 [22.0-37.8] vs 25.0 [20.0-31.3], P = .007) and gastrointestinal–fear of coronavirus-19 (15.0 [11.0-19.8] vs 12.0 [9.0-16.0], P = .02). Conclusion: Respondents with inflammatory bowel disease are more afraid of coronavirus-19 regarding their disease; especially, persons on sick leave or persons living in a rural setting. This should be taken into consideration to personalize the support that health care providers can offer in mitigating fear related to coronavirus-19. Cite this article as: Lo B, Barreiro-de Acosta M, Bernstein CN, et al. Fear of COVID-19 among patients with inflammatory bowel disease as compared to patients with other gastrointestinal conditions. Turk J Gastroenterol. 2022;33(8):664-672.